Fish oil replacement and alternative lipid sources in aquaculture feeds - Ng, Wing-Keong; Tocher, Douglas Redford; Turchini, Giovanni M. (CRC Press, 2011)
A comprehensive review on the multifaceted, complex issues relative to fish oil shortages and fish oil substitution in the formulation and production of feed for farmed aquatic species. It addresses crucial questions regarding the ability to meet increasing global demand for fisheries products